STUDI TENTANG EFEKTIFITAS KENAZIRAN HARTA WAKAF MENURUT UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF - Zahran R (Institut Agama Islam Negeri Bone, 2021)
AbstractProblems were oxplained through juridical normative juridical empiric, and syar’i approaches; and discussed through qualitative methods. Based on UU Nomor 41 Tahun 2004 about wakaf, wakaf management consists of organizer’s recruitment, competence and job realization. In the UU, organizer’s appointment is based on someone’s recruitmenr to be organizer through individual, organization and corporation; which are: Indonesia citizen, Moeslem, adult, trusted, healthy mind and body, not hampered to do law deed. Organizer’s competence must be considered to reach optimum management an the benefit. The tasks of organizers in UU are: to administer wakaf, t manage an develop wakaf based on function, to surprise and protect wakaf; and to report job implementation. Wakaf management in Watampone has been effective based on wakaf allocation which is traditional and consumptive because with or without organizer, consumptive wakaf like mosque still can operate; but it is not effective if it is related to wakaf regulation which hope that wakaf should be developed to be productive although the allocation is for mosque because modern and profesional mosque from wakaf can produce personal fee; so it needs trusted organizer, have competence and professional to manage it.